Sosialisasi Perundang-Undangan Transportasi - Putra, Agus Alisa; Desrimon, Arfi; Febrianty, Nanda Lelis (Journal of Social and Community Service, 2024)
This activity aims to socialize laws and regulations related to transportation in Koto Masjid Village, XIII Koto Kampar District, as a form of community service from the university. Traffic problems such as congestion, haphazard parking, and underage driving still occur due to a lack of legal awareness. This activity is expected to increase public understanding of transportation regulations and road safety. The methods used in this activity are field observation and interviews with community members as road users. The results of the observations indicate an imbalance between vehicle volume and road capacity, a lack of traffic signs, and traffic violations by teenagers and street vendors who use the road for trading. Solutions offered through this activity include socialization of traffic regulations, road safety education, and proposals for the addition and improvement of transportation facilities. It is hoped that this activity will increase public legal awareness and encourage the creation of safe and orderly traffic in the village environment.